Shared hotspot mutations in oncogenes position dogs as an unparalleled comparative model for precision therapeutics - Lucas Rodrigues; Joshua Watson; Yuan Feng; Benjamin Lewis; Garrett Harvey; Gerald Post; Kate Megquier; Michelle E. White; Lindsay Lambert; Aubrey Miller; Christina Lopes; Shaying Zhao (Scientific Reports, 2023)
Abstract Naturally occurring canine cancers have remarkable similarities to their human counterparts. To better understand these similarities, we investigated 671 client-owned dogs from 96 breeds with 23 common tumor types, including those whose mutation profile are unknown (anal sac carcinoma and neuroendocrine carcinoma) or understudied (thyroid carcinoma, soft tissue sarcoma and hepatocellular carcinoma). We discovered mutations in 50 well-established oncogenes and tumor suppressors, and compared them to those reported in human cancers. As in human cancer, TP53 is the most commonly mutated gene, detected in 22.5% of canine tumors overall. Canine tumors share mutational hotspots with human tumors in oncogenes including PIK3CA, KRAS, NRAS, BRAF, KIT and EGFR. Hotspot mutations with significant association to tumor type include NRAS G61R and PIK3CA H1047R in hemangiosarcoma, ERBB2 V659E in pulmonary carcinoma, and BRAF V588E (equivalent of V600E in humans) in urothelial carcinoma. Our findings better position canines as a translational model of human cancer to investigate a wide spectrum of targeted therapies.